2005
DOI: 10.1002/ijc.20860
|View full text |Cite
|
Sign up to set email alerts
|

Tumor HLA‐DR expression linked to early intrahepatic recurrence of hepatocellular carcinoma

Abstract: The outcome of patients with hepatocellular carcinoma (HCC) remains poor because of the high frequency of intrahepatic recurrence (IHR), particularly early IHR within 1 year of hepatectomy. To search for genes involved in early IHR, we performed DNA microarray analysis in a training set of 33 HCCs and selected 46 genes linked to early IHR from approximately 6,000 genes by means of a supervised learning method. Gene selection was validated by a false discovery rate of 0.37%. The 46 genes included many immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 35 publications
3
49
1
Order By: Relevance
“…This may explain why HCC patients with higher expression of MHC II genes have longer RFS time. This result partly agree with previous studies that have identified one or more MHC II molecules associated with the prognosis of HCC (14,(15)(16)(17)(18).…”
supporting
confidence: 93%
“…This may explain why HCC patients with higher expression of MHC II genes have longer RFS time. This result partly agree with previous studies that have identified one or more MHC II molecules associated with the prognosis of HCC (14,(15)(16)(17)(18).…”
supporting
confidence: 93%
“…In contrast, our univariate analysis showed increased levels of cfDNA in HCC patients with early IHR. Most early IHRs can be attributed to intrahepatic metastasis of cancer cells and are detected in 30 -50% of patients within 1 or 2 years after surgery, limiting the potential for surgical cure of HCC (Tung-Ping Poon et al, 2000;Iizuka et al, 2003;Llovet et al, 2003;Matoba et al, 2005;Portolani et al, 2006). Thus, the increased levels of serum cfDNA are related to the high metastatic potential, but not to the appearance of de novo tumour, of this type HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the remaining 87 patients were subjected to the following study. Patients were followed up as described previously (median follow-up time: 39 months) (Iizuka et al, 2003;Matoba et al, 2005). In brief, all 87 patients were followed up at least once every 3 months postoperatively by routine X-ray, ultrasonography (US), computed tomography, or magnetic resonance imaging, levels of serum a-fetoprotein and protein induced by vitamin K absence II (PIVKA-II) were also measured.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Several investigators, including ourselves, have identified gene signatures linked to HCC recurrence (6,(11)(12)(13)(14). Unfortunately, there was little overlap between the genes identified in the various studies, and interpretations of the data remain controversial (15).…”
Section: Introductionmentioning
confidence: 99%
“…These inconsistencies may be related to differences in the sample populations, use of distinct microarray platforms and algorithms, and the complicated modes of HCC recurrence (5 evaluating signature genes on the basis of the complicated recurrence modes of HCC. In the present study, to clarify the molecular features associated with EHR and early IHR of HCC, we investigated the genes linked to EHR of HCC in a supervised learning manner and then compared these genes with those linked to early IHR that was identified previously in the same manner (6,11).…”
Section: Introductionmentioning
confidence: 99%